Stability of Statics Aware Voronoi Grid-Shells. (1st June 2016) - Tonelli, D.; Pietroni, N.; Puppo, E.; Froli, M.; Cignoni, P.; Amendola, G.; Scopigno, R.
Highlights: A hex-dominant, statics aware remeshing pattern for free form grid-shells is proposed. Its structural efficiency was assessed through geometrically non-linear analyses. A comparative analysis was established between our and tri and quad grid-shells. Stability and imperfection sensitivity (shape and amplitude) were deeply investigated. Abstract: Grid-shells are lightweight structures used to cover long spans with few load-bearing material, as they excel for lightness, elegance and transparency. In this paper we analyze the stability of hex-dominant free-form grid-shells, generated with the Statics Aware Voronoi Remeshing scheme introduced in Pietroni et al. (2015). This is a novel hex-dominant, organic-like and non uniform remeshing pattern that manages to take into account the statics of the underlying surface. We show how this pattern is particularly suitable for free-form grid-shells, providing good performance in terms of both aesthetics and structural behavior. To reach this goal, we select a set of four contemporary architectural surfaces and we establish a systematic comparative analysis between Statics Aware Voronoi Grid-Shells and equivalent state of the art triangular and quadrilateral grid-shells. For each dataset and for each grid-shell topology, imperfection sensitivity analyses are carried out and the worst response diagrams compared. It turns out that, in spite of the intrinsic weakness of the hexagonal topology, free-form Statics Aware Voronoi Grid-Shells are much more effective than their state-of-the-art quadrilateral counterparts.